Computing Grounded Extensions Of Abstract Argumentation Frameworks. (28th November 2019) - Nofal, Samer; Atkinson, Katie; Dunne, Paul E
Abstract: An abstract argumentation framework is a directed graph (V, E) such that the vertices of V denote abstract arguments and E V × V represents the attack relation between them. We present a new ad hoc algorithm for computing the grounded extension of an abstract argumentation framework. We show that the new algorithm runs in O(|V|+|E|) time. In contrast, the existing state-of-the-art algorithm runs in O(|V|+|S||E|) time where S is the grounded extension of the input graph.